2017
DOI: 10.1007/s11920-017-0794-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Expression in Individuals With Schizophrenia and Healthy Aging: Testing the Accelerated Aging Hypothesis of Schizophrenia

Abstract: Individuals with schizophrenia show patterns of increased overall mortality, metabolic abnormalities, and cognitive decline normally observed later in life in the healthy population. An overall decrease is observed in BDNF expression in schizophrenia compared to healthy controls and in older individuals compared to a younger cohort. There is a marked decrease in BDNF levels in the frontal regions and in the periphery among older individuals and those with schizophrenia; however, data for BDNF expression in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 88 publications
1
32
0
Order By: Relevance
“…Furthermore, elevated hippocampal levels of BNDF have been reported (66). These changes are highly pertinent to schizophrenia, as NDMA hypofunction and decreased BDNF levels are thought to be involved in its pathogenesis, and its associated cognitive impairment (67).…”
Section: Prebiotics In Schizophreniamentioning
confidence: 99%
“…Furthermore, elevated hippocampal levels of BNDF have been reported (66). These changes are highly pertinent to schizophrenia, as NDMA hypofunction and decreased BDNF levels are thought to be involved in its pathogenesis, and its associated cognitive impairment (67).…”
Section: Prebiotics In Schizophreniamentioning
confidence: 99%
“…Morphological changes such as reduction in dendritic order and TDL have also been observed. These alterations coexist with the decline in the expression of neurotrophic factors, such as BDNF and an increase in reactive astrogliosis (Islam, Mulsant, Voineskos, & Rajji, ; Jyothi et al, ). All this is an indication of the evolution of a neurodegenerative process in limbic regions culminating with neuronal death and the deterioration of spatial and/or recognition memory (Diaz et al, ; Johnson et al, ; Vidal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF has a role in regulating the secretion of neurotransmitters with a key effect on serotonergic, dopaminergic, glutamatergic, and plasticity mechanisms such as long-term potential and mechanisms in learning and memory [9]. Many studies have shown a close link between BDNF and some diseases like schizophrenia, Alzheimer's disease, mood disorders, and Parkinson's disease [10][11][12][13][14]. Some studies have shown that BDNF probably has a necessary role in neuroimmune regulation of mood disorders.…”
Section: Introductionmentioning
confidence: 99%